The Influence of Service Quality and Qris on Claudia Laundry's Customer Satisfaction - Sriwardani, Komang Novi (Jurnal Locus Penelitian dan Pengabdian, 2025)
This study aims to determine the influence of service quality and the use of QRIS on customer satisfaction of Claudia Laundry in Sawan Village. This study uses a quantitative method with a survey approach. The study population was Claudia Laundry's regular customer as many as 125 people, with a sample of 96 respondents taken using the slovin formula and purposive sampling technique. The data analysis technique used was multiple linear regression. The results of the study show that the quality of service and the use of QRIS simultaneously or partially have a positive and significant effect on customer satisfaction. Service quality has the most dominant influence on customer satisfaction. This research provides recommendations for laundry entrepreneurs to improve services and provide a digital payment system.